2015
DOI: 10.3324/haematol.2015.124651
|View full text |Cite
|
Sign up to set email alerts
|

Four genes predict high risk of progression from smoldering to symptomatic multiple myeloma (SWOG S0120)

Abstract: © F e r r a t a S t o r t i F o u n d a t i o nGenomics of high-risk SMM haematologica | 2015; 100(9) 1215 Methods Eligibility criteria and study designPatients with SMM seen at the Myeloma Institute for Research and Therapy were included in a prospective, observational clinical trial (SWOG S0120) as part of a national cooperative group trial to identify biological correlates that may relate to progression to symptomatic disease. Other eligibility criteria included no prior therapy for the plasma cell disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…In addition, the Arkansas group generated a risk-stratification model based on expression levels of only four genes combined with serum M-protein (≥30 g/L) and albumin levels (<35 g/L). The high-risk, intermediaterisk, and low-risk groups had a 2-year progression probability of 5.0%, 44.8%, and 85.7%, respectively [54].…”
Section: Prediction Models In Smmmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the Arkansas group generated a risk-stratification model based on expression levels of only four genes combined with serum M-protein (≥30 g/L) and albumin levels (<35 g/L). The high-risk, intermediaterisk, and low-risk groups had a 2-year progression probability of 5.0%, 44.8%, and 85.7%, respectively [54].…”
Section: Prediction Models In Smmmentioning
confidence: 98%
“…Other factors that predict progression to symptomatic disease include abnormal plasma cell phenotype in ≥95% of cells, high plasma cell proliferative rate, hypogammaglobulinemia, gene expression profile of the purified MM cells, abnormal free lightchain ratio, increasing M-protein, presence and development of MRI abnormalities, or peripheral blood circulating plasma cells [27,43,44,[49][50][51][52][53][54]. Also, hyperdiploidy, del(17p), t(4;14), and ampl(1q) are adverse prognostic factors in SMM, independent of tumor load [55,56] (Figure 1).…”
Section: Progression O F Smmmentioning
confidence: 99%
“…The RNA-sequencing have been created and will be incorporated into GEP to enhance estimation of the outcome in the future [98]. Of these modifiers, non-coding RNA are mainly researched in MM since reports have already proved that micro-RNA contribute to myeloma formation and can be used to predict prognosis or response to auto-transplant [98]. MiR17 and miR886-5p have been observed as a strong prognostic indicator in a study of 163 newly diagnosed patients from the MRC Myeloma IX l trial [99].…”
Section: Transcriptome Modifiers Profilingmentioning
confidence: 99%
“…Investigators from UAMS has reported that 70-genes signature and its derivative are able to predict outcome in context of MGUS and SMM (23). In the context of PCL, in a cohort of 21 patients, a 27 gene expression signature was identified as an independent prognostic factor (24).…”
Section: Gep and Prognosticationmentioning
confidence: 99%